Technological Innovation in Public Administration Transformation: Case Study of e-Government Implementation in Indonesia - Arief Prayitno (Universitas Sultan Ageng Tirtayasa, 2023)
This research investigates the impact of technological innovation on the transformation of public administration through the implementation of e-government in Indonesia. The main objective of this research is to analyze the extent to which the implementation of e-government has contributed to efficiency, transparency, and community involvement in the delivery of public services. The research methodology involves a case-study approach to e-government implementation at various levels of government in Indonesia. The results of this research highlight the positive impact of information and communication technology (ICT) innovation in the transformation of public policy, especially in Indonesia. The digitalization of public services, increasing transparency and public participation through social media, efficiency and cost savings through process automation, and efforts to increase data security are key points that support the transformation of public administration. The implementation of e-government in Indonesia, driven by central government policy, reflects efforts to improve services, efficiency, and community involvement. However, challenges such as the digital divide, resistance to change, legal and regulatory issues, and the need for inclusive public participation are things that need to be considered in implementing ICT innovation in public policy. Taking these challenges into account, this research concludes that ICT innovation can be a significant driver in achieving positive transformation in public administration, provided that it is necessary to overcome the obstacles that arise.